2022
DOI: 10.12845/sft.59.1.2022.3
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of Using Mobile Fans and the Parameters Conditioning the Effectiveness of Tactical Mechanical Ventilation

Abstract: Aim: The aim of the article is to indicate the possible scope of application of mobile fans during the execution of rescue actions and identification of the parameters conditioning the effectiveness of using this type of units. Method Design: Mobile overpressure fans are a tool used during rescue operations mainly to remove hot gases and smoke, which accumulate in confined spaces covered by fire – primarily within the evacuation routes, but also in the rooms. In literature there are examples of other uses of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Proper positioning of the ventilator, selection of openings (air mass inlet and outlet), making the gas exchange path, monitoring environmental conditions (e.g. wind influx) is an important aspect of the rescue operations in progress 2 . Focusing on the issue of positioning the mobile ventilator, it should be emphasized that the positive pressure ventilator should be positioned in such a manner in which it works most efficiently, which is measured by assessing the volume flow rate injected into the building volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper positioning of the ventilator, selection of openings (air mass inlet and outlet), making the gas exchange path, monitoring environmental conditions (e.g. wind influx) is an important aspect of the rescue operations in progress 2 . Focusing on the issue of positioning the mobile ventilator, it should be emphasized that the positive pressure ventilator should be positioned in such a manner in which it works most efficiently, which is measured by assessing the volume flow rate injected into the building volume.…”
Section: Introductionmentioning
confidence: 99%
“…Achieved air flow rates for the tested configurations(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), where AVGarithmetic mean of the flow rate (m 3 /h) and confidence interval (p=0.05).…”
mentioning
confidence: 99%
“…and under pressure ventilation (PPV), positive pressure attack (PPA), assisting evacuation from a re-affected facility, suppressing res of freestanding structures, etc. 37 .…”
Section: Introductionmentioning
confidence: 99%
“…To combat the risk of smoke during internal fires, firefighters use mobile fans taking into account various mechanical ventilation techniques, e.g., positive pressure ventilation (PPV) or negative pressure ventilation 6 . The literature on the subject also indicates other possibilities of using these devices, respectively: supporting activities related to the elimination of fire hazards of free-standing objects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on the subject also indicates other possibilities of using these devices, respectively: supporting activities related to the elimination of fire hazards of free-standing objects (e.g. cars or garbage containers), ventilation of hard-to-reach places (where people stay)—with the use of electric fans 6 . Referring to devices (including positive pressure ventilators) used in rescue operations, it is indicated that they should be characterized by high operational reliability, efficiency, and functionality and should have little impact on the user 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%